2018
DOI: 10.1111/cei.13167
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 inflammasome activation contributes to the pathogenesis of rheumatoid arthritis

Abstract: Summary Nucleotide‐binding, oligomerization domain (NOD)‐like receptor family, pyrin domain containing 3 (NLRP3) gene polymorphism was reported to be associated with susceptibility, disease activity or anti‐tumour necrosis factor (TNF) treatment response in rheumatoid arthritis (RA). However, the roles of NLRP3 inflammasome in the development of RA have not yet been elucidated fully. The present study aimed to study the role of NLRP3 inflammasome in RA. NLRP3 inflammasome activation in synovial tissues from RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
180
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(210 citation statements)
references
References 47 publications
2
180
1
1
Order By: Relevance
“…NLRP3 inflammasome is also a key tissue damage sensor. The past decade has witnessed many studies, which suggested that the malfunction of NLRP3 inflammasome is a potent trigger of a series of autoinflammatory and autoimmune diseases, including gout, rheumatoid arthritis, and lupus . Moreover, NLRP3 inflammasome has been reported to participate in the chronic inflammation status in the prostate …”
Section: Introductionmentioning
confidence: 99%
“…NLRP3 inflammasome is also a key tissue damage sensor. The past decade has witnessed many studies, which suggested that the malfunction of NLRP3 inflammasome is a potent trigger of a series of autoinflammatory and autoimmune diseases, including gout, rheumatoid arthritis, and lupus . Moreover, NLRP3 inflammasome has been reported to participate in the chronic inflammation status in the prostate …”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that inflammasome activation may contribute to pro-inflammatory cytokine secretion in RA patients making inflammasome inhibition a possible therapeutic strategy in the future treatment of RA. In line with this, Guo et al demonstrated the NLRP3 inflammasome to be strongly activated both in synovia of RA patients and in an in vivo mouse model of collagen-induced arthritis [309]. Here, treatment with MCC950, a selective NLRP3 inhibitor, resulted in both significantly reduced joint inflammation and bone destruction as well as reduced production of IL-1β in vivo [310].…”
Section: Inhibition Of Nod- Lrr- and Pyrin Domain-containing Proteimentioning
confidence: 87%
“…Genetic variants within the NLRP3-inflammasome are associated with susceptibility to RA [97][98][99][100][101], and enhanced activity of NLRP3 inflammasome has been found in peripheral blood cells of patients with active RA [102]. Inhibition of NLRP3 inflammasome activity alleviated arthritis in CIA mice [103]. Given that NLRP3 was one of the PR-targeted gene [34] and that the lack of PR potentiated NLRP3 inflammasome expression in the synovial tissue of the CIA mice, suggesting that although PR might not alter the underlying cause of disease, it might reduce the production of factors such as inflammasomes which are involved in inflammation, cartilage and bone destructions in RA.…”
Section: Discussionmentioning
confidence: 99%